Passion Berwirausaha pada Pengusaha Muda - Petra Merieska; IJK Sito Meiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This study aims to understand understanding the dynamics of passion in youth entrepreneurs when running a business. By understanding the dynamics of passion in running a business, youth entrepreneurs can understand the importance of passion's role in his business so as to avoid failure. In order to achieve these objectives, a phenomenological study was conducted on purposively selected participants, ie nascent new business entrepreneurs who have a passion for entrepreneurship aged 18 to 34years. Data were collected using semi-structured phenomenological interviews and analyzed using a phenomenological analysis approach. The results show that the dynamics of passion play an important role in the three series of areas of entrepreneurial activity: 1) product creation and development, 2) business establishment, 3) business development. While also found the aspects of personal, environmental and behavior that affect the emergence of entrepreneurial passion on them.